Toleransi Pascakonflik di Tobelo - H. Hans Panjaitan (Societas Dei: Jurnal Agama dan Masyarakat, 2018)
ABSTRACT: This article on "Tolerance of Interfaith Conflict in Tobelo" will measure the level of religious tolerance in Tobelo District to see the current state of religious tolerance in Tobelo. This study was conducted in the form of a survey of high school students in Tobelo District. Tobelo student's opinion can be a gauge to see the level of religious tolerance in Tobelo. The findings of this research are: high levels of interreligious tolerance in Tobelo, but based on data on integration surveys among community groups that have been involved in the conflict must still be improved to foster mutual trust among different religious groups. Therefore, the research recommendation is that local governments should continue to foster the spirit and spirit of tolerance among religious followers by, for example, building diverse communities of religions, especially within the scope of education.KEYWORDS: tolerance, conflict, religion, tolerance education, TobeloABSTRAK: Artikel "Toleransi Pascakonflik Antaragama di Tobelo" ini akan mengukur tingkat toleransi beragama di Kabupaten Tobelo untuk melihat kondisi terkini terkait tingkat toleransi beragama di Tobelo. Penelitian ini dilakukan dalam bentuk survei terhadap siswa sekolah menengah atas di Kabupaten Tobelo. Pendapat siswa Tobelo dapat menjadi alat ukur untuk melihat tingkat toleransi beragama di Tobelo. Temuan penelitian ini adalah: tingkat toleransi antaragama di Tobelo tinggi, namun berdasarkan data survei integrasi antar-kelompok masyarakat yang pernah terlibat konflik itu masih harus ditingkatkan untuk menumbuhkan rasa saling percaya antar-kelompok masyarakat yang berbeda agama. Karena itu saran penelitian ini adalah pemerintah daerah sepatutnya terus menumbuhkan jiwa dan semangat toleransi di antara pemeluk agama dengan misalnya, membangun komunitas-komunitas beragam agama, khususnya dalam lingkup pendidikan.KATA-KATA KUNCI: toleransi, konflik, agama, pendidikan toleransi, Tobelo